2010
DOI: 10.1074/jbc.m110.104919
|View full text |Cite
|
Sign up to set email alerts
|

d-Maurocalcine, a Pharmacologically Inert Efficient Cell-penetrating Peptide Analogue

Abstract: Maurocalcine has been the first demonstrated animal toxin acting as a cell-penetrating peptide. Although it possesses competitive advantages, its use as a cell-penetrating peptide (CPP) requires that analogues be developed that lack its characteristic pharmacological activity on ryanodine-sensitive calcium channels without affecting its cell-penetrating and vector efficiencies. Here, we present the synthesis, three-dimensional 1 H NMR structure, and activity of D-maurocalcine. We demonstrate that it possesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…The second strategy, which has yield success, is based on the chemical synthesis of D-MCa, an analogue entirely based on the use of D-amino acids. This peptide is a mirror image of the natural L-MCa but, like other D-CPPs, preserves its cell penetration properties while losing entirely its ability to interact with RyR1 (19). This method has several advantages.…”
Section: Maurocalcine (Mca)mentioning
confidence: 99%
See 2 more Smart Citations
“…The second strategy, which has yield success, is based on the chemical synthesis of D-MCa, an analogue entirely based on the use of D-amino acids. This peptide is a mirror image of the natural L-MCa but, like other D-CPPs, preserves its cell penetration properties while losing entirely its ability to interact with RyR1 (19). This method has several advantages.…”
Section: Maurocalcine (Mca)mentioning
confidence: 99%
“…Solid Phase Peptide Syntheses-Chemical syntheses of MCa analogues were performed as described previously (19). Briefly, analogues of MCa were chemically synthesized by the solid phase method (20) using an automated peptide synthesizer (CEM© Liberty).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-penetrating peptides (CPPs) are peptides which enter into cells and allow the intracellular delivery of a number of bioactive molecules such as proteins, peptides, oligonucleotides, and nanoparticles [1][2][3]. Originally isolated from the venom of the scorpion Scorpio maurus palmatus [4], Lmaurocalcine (L-MCa) is an animal toxin acting as a highly efficient CPP [5][6][7][8]. It presents a low toxicity profile, penetrates at lower concentrations, and efficiently accumulates into the cytoplasm which is a highly desirable quality for many applications involving CPPs.…”
Section: Introductionmentioning
confidence: 99%
“…These observations have prompted us to investigate the cell penetration properties of maurocalcine. A series of studies have demonstrated since 2005 that maurocalcine belongs to the cell penetrating peptide family with vector properties that can be derived for various diagnostic, imaging and therapeutic applications (Aroui et al, 2009;Boisseau et al, 2006;Esteve et al, 2005;Jayagopal et al, 2009;Mabrouk et al, 2007;Poillot et al, 2010). A more detailed investigation of the mode of action of maurocalcine in developing skeletal muscle cells and adult fibers reveals that the peptide acts preferentially on type 1 ryanodine receptors that are uncoupled from the L-type calcium channels (Szappanos et al, 2005).…”
Section: Use Of Maurocalcine To Understand Excitation-contraction Coumentioning
confidence: 99%